2021
DOI: 10.1089/thy.2020.0596
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Thyroid Function Predict Cognitive Decline in the Very Old: Longitudinal Findings from the Newcastle 85+ Study

Abstract: Background: Low serum thyrotropin (TSH) has been associated with an increased risk of cognitive impairment in observational studies of older individuals, but the mechanism underlying this is unclear. We investigated the association between changes in thyroid status and cognitive impairment in very old adults, using prospective data from the Newcastle 85+ study. Method: A cohort of 85-year-old individuals was assessed for health status and thyroid function. Complete data from a comprehensive multidimensional me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This study's main aim was to explore the causal relationships between thyroid function and AD with the use of bidirectional MR techniques. We showed that increased levels of genetically predicted TSH within the normal range were significantly associated with a decreased risk of AD, in agreement with previous evidence (5,7,8). We further explore the effect of full range TSH levels on AD risk by using summary statistics from different data sets, including data from the largest meta-analysis from HUNT+MGI+ThyroidOmics along with analyses only using data from the HUNT study, as a more homogeneous set.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study's main aim was to explore the causal relationships between thyroid function and AD with the use of bidirectional MR techniques. We showed that increased levels of genetically predicted TSH within the normal range were significantly associated with a decreased risk of AD, in agreement with previous evidence (5,7,8). We further explore the effect of full range TSH levels on AD risk by using summary statistics from different data sets, including data from the largest meta-analysis from HUNT+MGI+ThyroidOmics along with analyses only using data from the HUNT study, as a more homogeneous set.…”
Section: Discussionsupporting
confidence: 83%
“…Another study by van Osch et al (4) also found that lower TSH levels within the reference range were associated with an increased AD risk; however, in contrast to the Framingham study, these results were independent of sex. Gan et al report that with older age, the feedback between TSH and fT4 attenuates (7). Thus, decreased TSH is associated with decreased fT4, which is associated with cognitive decline.…”
mentioning
confidence: 99%
“…(31) In older populations (85 years), a longitudinal decrease in TSH levels was associated with a concomitant reduction in MMSE scores over a three-and five-year follow-up period. (32) Thyrotoxicosis is a rarer condition in which patients present very high thyroid hormones either of endogenous or exogenous etiology (corresponding to very low TSH). In a study including 65931 elderly patients aged 65 years and older, thyrotoxicosis was associated with a significantly higher risk of cognitive decline.…”
Section: Thyroid Function and Cognitionmentioning
confidence: 99%